218k views
1 vote
Write the expression as a single logarithm.

Write the expression as a single logarithm.-example-1
User Etna
by
4.5k points

1 Answer

5 votes


\bf \begin{array}{llll} \textit{logarithm of factors} \\\\ \log_a(xy)\implies \log_a(x)+\log_a(y) \end{array} ~\hspace{4em} \begin{array}{llll} \textit{Logarithm of exponentials} \\\\ \log_a\left( x^b \right)\implies b\cdot \log_a(x) \end{array} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ 3\log_b(q)+6\log_b(v)\implies \log_b(q^3)+\log_b(v^6)\implies \log_b(q^3v^6)

User Joakim Berglund
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.